PENGARUH PRECONDITIONING PADA PENGUJIAN BEBAN BERULANG BAHAN BERBUTIR TANPA PENGIKAT - Djoko Widajat (Jurnal Jalan-Jembatan, 2006)
Two variations of preconditioning are given for repeat loading test unbound material are1000 cycles and 100 cycles. The change of the confining pressure and total axial stress after each preconditioning, creates drop on the value of the strains increment. The proportion of dropping value for resilient strain is lower for 100 cycles than 1000 cycles preconditioning, from the equally lines. Whereas, the different between permanent strains increment for both preconditioning are not too significant. It shows that the resilient increment strains drop for 100 cycles smaller than 1000 cycles. Increasing the total number of pulses or cycles will influence on the increasing the increment of strains, the proportion of increment tend to become higher by increasing the cycles.